Discovery Learning with Traditional Educational Game Gobak Sodor in Physical Education Learning - Indra Adi Budiman (AL-ISHLAH: Jurnal Pendidikan, 2024)
Physical education aims to improve both physical fitness and social skills. Discovery Learning in physical education, rooted in a constructivist approach, fosters active exploration, problem-solving, and understanding through direct experiences. Incorporating traditional educational games like Gobak Sodor serves as an effective model for achieving these dual objectives. A mixed-methods approach was employed, utilizing Embedded Design to combine qualitative and quantitative data for a comprehensive analysis. The study involved 32 seventh-grade students from SMPN 3 Majalengka. Qualitative data were gathered through interviews and observations, while quantitative data were collected using physical fitness tests (endurance, strength, agility) and questionnaires. Social skills were evaluated based on communication, cooperation, empathy, and conflict resolution. The implementation of Discovery Learning with the Gobak Sodor game significantly enhanced students' physical fitness and social skills. Improvements were observed in endurance, strength, and agility, alongside better communication, cooperation, and empathy among students. The findings highlight the effectiveness of traditional educational games in achieving physical and social development in physical education settings. However, further research is recommended to explore the application of this method in diverse student populations to confirm its broader applicability. Discovery Learning with the Gobak Sodor game positively impacts students’ physical fitness and social skills. Expanding this approach to other contexts could provide valuable insights for educational innovation.